Treatment-resistant depression with anhedonia: Integrating clinical and preclinical approaches to investigate distinct phenotypes. (May 2022) - Kelly, Chris A.; Freeman, Kevin B.; Schumacher, Julie A.
Abstract: In our clinical work with treatment-resistant depressed (TRD) patients, certain patterns have emerged in terms of patients' presentations of anhedonia. Multiple studies have investigated anhedonia either as a state or a trait variable in depression, but anhedonia is a multifaceted construct and, as we better understand anhedonia, we increase our ability to measure and treat it. With the aim of personalizing medicine for more efficacious treatments, this paper focuses on clinical patterns we have seen in anhedonic TRD and argues for studies to be done in support of translational, face, and construct validity. Three representative clinical presentations of TRD with anhedonia are described: a congenital type, a stress-induced type, and a type exacerbated by medication. Each case is followed with discussion relating the clinical features to clinical and preclinical research relevant to putative mechanisms for the case. Animal models that are best suited to investigate and validate the existence of etiologies and mechanisms underlying anhedonia constructs unique to each case are proposed, as are potential directions for research in humans. Highlights: Anhedonic heterogeneity may contribute to depression heterogeneity and inadequate response to treatment. Clinical patterns of anhedonia can be back translated to discover neurobiological underpinnings of depression endophenotypes. Composite case clinical presentations of anhedonia in TRD are reviewed as bases for future preclinical and human research.